Ukraine Innovation and Entrepreneurship Ecosystem Diagnostic - World Bank (World Bank, Washington, DC, 2017)
This report is one of four analytical pieces on Ukraine’s innovation and entrepreneurial ecosystem developed by the World Bank’s Ukraine Technical Assistance on Innovation, supported by the Swedish Ukraine Financial and Enterprise Sector Recovery and Growth Trust Fund. This report assesses the environment – or “ecosystem” -- that shapes innovation by firms in Ukraine. It examines the ecosystems for three categories of companies: existing Ukrainian companies, new start-ups, and international companies investing in Ukraine. Based on a review of prior literature and approximately 50 interviews with representatives from industry, academia, and government, it systematically examines how industry and market structure, government policies and regulations, human capital, research and knowledge transfer, infrastructure and support programs, and finance all affect innovation in Ukraine. The report notes that Ukraine has improved its business environment and has significant strengths in well-educated workforce. A relatively large and growing market, abundant resources, and low costs at current exchange rates all favor foreign investments that will support innovation. But Ukraine also faces many challenges. Industrial R&D is low and declining (due to industry’s concentration in low R&D sectors) and there is a lack of competition and market demand to drive.